Strengthening Tax Accounting Literacy and Assisting MSMEs in Preparing Financial Statements in Cikarageman Village for Access to Credit and Digital Financing - Prisila Damayanty; Indra Setiawan; Kampono Imam Yulianto; Triyono Adi Tristanto; Dadan Sundara; Zara Tania Rahmadi; Ofy Dwilestari; Alifia Winarti; Sinta Amelia Putri; Shashtya Rea Hasanah; Khayra Shinta Audry (International Journal Of Community Service, 2026)
This research aims to provide an understanding of the importance of Strengthening Tax Accounting Literacy and Assisting MSMEs in Preparing Financial Statements in Cikarageman Village for Access to Credit and Digital Financing. Through this program, MSME actors are equipped with basic knowledge of tax accounting and technical assistance in preparing financial statements that are accountable, transparent, and in accordance with applicable standards. This is conducted to improve business eligibility in accessing banking credit facilities and digital financing platforms that require complete financial administration. In addition, this activity also disseminates the urgency of tax compliance for MSMEs as part of good and sustainable business governance. The method used was a participatory educational approach consisting of outreach, practical training, and direct mentoring conducted in a single face-to-face session, complemented by pre-test and post-test assessments to measure participants' improvement in understanding. The results of the program indicate that participants demonstrated improved understanding of tax accounting, financial reporting, Good Corporate Governance (GCG), and entrepreneurial motivation. The availability of well-structured financial statements and improved governance practices enhanced MSMEs' readiness to access formal credit and digital financing while promoting greater tax awareness. Thus, this program contributes to strengthening the digital economic ecosystem at the village level.